Activation of nitrite by freezing process for anaerobic digestion enhancement of waste activated sludge: Performance and mechanisms - Liu, Xuran; Huang, Xiaoding; Wu, Yanxin; Xu, Qiuxiang; Du, Mingting; Wang, Dongbo; Yang, Qi; Liu, Yiwen; Ni, Bing-Jie; Yang, Guojing; Yang, Fan; Wang, Qilin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Freezing activated nitrite pretreatment (FN) enhanced anaerobic digestion from WAS.•FN benefited WAS disintegration and the biodegradable of organics released.•FN benefited the dewaterability or pathogens inactivation of digested sludge.•Freezing induced reactive derivatives from nitrite were the major contributors.•FN was economically and environmentally attractive. Nitrite-based pretreatment was demonstrated to effectively improve anaerobic digestion of waste activated sludge. It was found in this work that the freezing activated nitrite pretreatment could further enhance the performances. With the increase of nitrite addition from 0 to 600 mg NO2−-N/L during freezing process, the biochemical methane potential of pretreated-sludge gradually increased from 191.3 ± 8.0 to 233.2 ± 10.6 mL per gram volatile solid (VS), while only 178.6 ± 7.3 mL/g VS was obtained in the raw sludge. Mechanism explorations revealed that the freezing activated nitrite pretreatment remarkably facilitated the disintegration of sludge. Excitation emission matrix and fluorescence regional integration analyses further revealed that nitrite addition during freezing process promoted the proportion of biodegradable organics released, thereby providing more bio-available substrates for subsequent anaerobic digestion. Freezing condition induced reactive derivatives from nitrite (e.g., free nitrite acid, NO2, N2O3) were assumed to be the major contributors to the enhanced sludge disintegration and recalcitrant organics (e.g., humic acid-like substances) degradation. It was also found that 600 mg NO2−-N/L addition activated by freezing pretreatment produced an anaerobically digested sludge with an improved dewaterability, as indicated by the decrease of the specific resistance to filterability and moisture content of dewatered cake. Moreover, 600 mg NO2−-N/L addition activated by freezing pretreatment and subsequent anaerobic digestion largely inactivated the pathogens to the levels below Class A biosolids requirements. Considering that nitrite can be in-situ produced in wastewater treatment plants through nitritation of the digestion liquid, this nitrite-based freezing process for sludge pretreatment was environmental-friendly and economically attractive.